The Physician’s Pure Land - Briana Brightly (Asian Medicine, 2026)
Abstract Tanaduk refers to the realm of the Medicine Buddha that was first introduced in the Four Tantras . This article explores how, in early modern Tibet, Tanaduk emerged as both a Buddhist pure land and model of an ideal natural order. Even as its existence remained contested in the Tibetan medical community, Tanaduk persisted as a medical paradigm that physicians sought to realize in their own surroundings. I argue that the project of seeing the world through the mirror of the pure land was pursued in tandem with the investigation of nature. Here, Tanaduk provided a framework for ordering the natural world; but it was a framework in flux, a product of the physician’s inquiry as much as it was a guide to it. As this article contends, Tanaduk was not merely an object of theoretical speculation but a generative cosmology for Tibetan medicine.